Optimizing the Realization of Non-Performing Assets in Commercial Banks: Operational and Process Improvement Approaches - Temirov Abdumalik Temirovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: Non-performing assets (NPAs) represent a critical challenge for commercial banks, adversely impacting liquidity, profitability, and credit extension. Traditional legal and financial measures, while necessary, often fail to address inefficiencies in operational processes, leading to delayed recovery and increased costs. This study investigates operational and process improvement strategies that enhance NPA realization. A mixed-methods approach, including portfolio analysis and structured interviews with 50 banking professionals, was employed to examine bottlenecks, workflow inefficiencies, and technology integration. Findings indicate that structured workflows, early-warning monitoring systems, and digital recovery platforms significantly improve realization rates, reduce processing time, and increase operational efficiency. The study provides a comprehensive operational framework for banks seeking to optimize NPA recovery.